Potential limitation of organic fertilizer for crop productivity improvement an analysis of detailed farming record in Tamil Nadu, India from 1993 to 2003 - Palanichamy, N. Venkatesa; Kajisa, Kei (2010)
Amidst the increasing attention to utilization of organic fertilizer, there are mixed opinions on its importance for crop productivity improvement, This paper explores the potentials and limitations of the use of farmyard manure (FYM) on different crops under different soil conditions in Tamil Nadu, India, using farming households' three-year to rotating panel from 1993 to 2003.
Estimate yield functions reveal that the direct impact o FYM application exists only for upland cereals but not for paddy. Meanwhile, an indirect impact (i.e., increase in the marginal product of chemical fertilizer) is observed both for paddy and upland cereals, especially under low inherent soil fertility status. On the other hand, the factor demand estimation shows that farmers react to FYM price changes more intensely for upland cereal production than they do for paddy production, thus reinforcing the previous finding of a stronger physical impact of FYM application on upland cereals. The findings imply that, through the FYM market, dairy sector development and the associated increase in the availability of FYM contribute toward the productivity improvement o tp kind of poverty-prone areas: 1) upland cereal production area; and 2) areas of inherently poor social condition. However, the price transmission analysis finds that, due to the nontradable attribute of FYM, such impact is spatially constrained within a village where dairy sector development has taken place and is thus the limitation of the FYM-based development strategy.
Keywords: Fertilizers and manures; Fertilizers; Organic fertilizers